Pedoenvironmental indicators of soil in Western Amazonia, Brazil - Oliveira, Ivanildo Amorim de; Costa Campos, Milton Cesar; Siqueira, Diego Silva [UNESP]; Freitas, Ludmila de; Aquino, Renato Eleoterio de [UNESP]; Oliveira, Flavio Pereira de (Springer, 2020)
This study aimed to ascertain what soil attributes may be an indicator of natural and anthropic pedogenic changes in top grassland (TG), low grassland (LG), ecotone zone (EZ), and forest (F) in Western Amazonia. Twenty samples of the diagnostic horizons were collected from the studied pedoenvironments: TG (A 0.0-14 and Bi 0.30-0.66 m); LG (A 0.0-0.15 and C-g1 0.27-0.80 m); EZ (A 0.0-0.15 and Bi 0.32-0.50 m); and forest (F) (A1 0.0-0.15 and B-t1 0.67-0.10 m). Sand, silt, clay, particle density (PD),soil bulk density (BD),saturated soil hydraulic conductivity, calcium (Ca), magnesium (Mg), exchangeable aluminum (Al3+), potassium (K), sodium (Na), phosphorus (P), pH in water and KCl, and organic matter (OM) contents were calculated and submitted to variance analysis. LG is more related to OM and clay than SHC value. These same attributes characterized TG. EZ is highlighted by its higher values and relationship with Al and K. It was concluded that for TG, LG, EZ, and F top soil layers, 28% of natural and anthropic changes can be identified based on sand, clay, pH in KCl, and OM data; on the other hand, subsurface 23% of determinations can be attributed to pH in H2O, Al, Na, and sand.
Keywords: Pedoindicators; Soil attribute; Multivariate analysis; Inceptsol; Aqualf; Alfisols